Manajemen Kurikulum Berbasis Kitab Kuning di Ma’had Aly Pondok Pesantren Darussalam Blokagung Tegalsari Banyuwangi - Ahmad Shodiq Pratama; Imron Fauzi (Postgraduate Study Programme, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Ma'had Aly Darussalam Blokagung is one of the Ma'had Alys who is quite successful in managing the yellow book-based curriculum, this is proven by the many graduates who have become religious figures in society and have achieved many achievements. The Ma'had Aly Darussalam curriculum focuses on preserving Islamic boarding school traditions and innovating educational methodologies to produce quality scholars. The focus of this research is 1) How is the yellow book-based curriculum planned at Ma'had Aly Islamic Boarding School Darussalam, 2) How is the yellow book-based curriculum implemented at Ma'had Aly Darussalam Islamic Boarding School, 3) How is the yellow book-based curriculum evaluated in Ma'had Aly Darussalam Islamic Boarding School. The objectives to be achieved by the researcher are 1) Describe the planning of the yellow book-based curriculum at Ma'had Aly Pondok Pesantren Darussalam, 2) Describe the implementation of the yellow book-based curriculum at Ma'had Aly Pondok Pesantren Darussalam, 3) Describe the evaluation of the yellow book-based curriculum in Ma'had Aly Darussalam Islamic Boarding School. The approach in this research is descriptive qualitative, the data collection techniques used are in-depth interviews, observation and documentation. The collected data is then analyzed using analytical techniques which include data collection, data condensation, data presentation, conclusion verification, then the validity of the data is tested using data source triangulation techniques, method triangulation, theory triangulation, discussions with colleagues and holding member checks. The conclusions of this research are 1). Yellow book-based curriculum planning at Ma'had Aly Darussalam includes planning the vision, mission and goals, curriculum content, teaching materials or learning resources, learning methods and models, and evaluation. 2). The implementation of the curriculum at Ma'had Aly Darussalam includes the implementation of learning content, learning methods and models. 3). Curriculum evaluation at Ma'had Aly Darusslam consists of monthly and annual evaluations which include several points; learning evaluation, mahasantri evaluation, evaluation of the selection of new mahasantri, evaluation of improving the quality of Sufism and tarekat learning models, and evaluation of services and human resources.